Novel Application of an Ultrasonic Bone Aspirator for Endoscopic Modified Medial Maxillectomy - Takakura, Hiromasa; Tachino, Hirohiko; Oi, Yutaro; Do, Tram Anh; Shojaku, Hideo (Frontiers in Surgery, 2022)
Background: EMMM is a surgical technique developed to approach maxillary sinus lesions, such as papilloma and postoperative maxillary cyst (PMC), while preserving the postoperative nasal morphology and nasal function. In this technique, a diamond burr is used to remove the bone, which may damage adjacent soft tissue. We developed EMMM using an ultrasonic bone aspirator (UBA) instead of a conventional diamond burr. The purpose of this study was to clarify the effectiveness of the UBA in EMMM in comparison to the conventional diamond burr technique in terms of operative time, intraoperative complications, postoperative symptoms, and recurrence. Methods: The medical records of all patients who underwent EMMM at Toyama University Hospital between June 2014 and December 2021 were reviewed. Patients who met the inclusion criteria were separated into Group 1, in which the UBA was used for EMMM and Group 2, in which a drill with a diamond burr was used. Data on patient demographics, operation time, frequency of intraoperative complications and postoperative symptoms, and recurrence were statistically compared between the two groups. Results: There were no significant differences between the two groups in the patient demographic data, operative time, postoperative symptoms, or frequency of recurrence. The frequency of intraoperative damage to adjacent soft tissues was significantly lower in patients who underwent EMMM with the UBA in comparison to those who underwent EMMM with a conventional diamond burr. Conclusion: The application of the UBA to EMMM can improve surgical safety and facilitate surgical procedures.